Ownership control and debt maturity structure: evidence from China. Issue 3 (27th May 2014) - Ruan, Wenjuan; Cullen, Grant; Ma, Shiguang; Xiang, Erwei
Abstract : Purpose: – The authors examine the debt maturity structure of Chinese listed companies during the period when bond market was under-developed and the majority of commercial banks were owned by the state. The purpose of this paper is to answer why and how the different ownership control types impact the firms' preference and accessibility to either long- or short-term debts. Design/methodology/approach: – The univariate analysis was used to test the differences of debt maturity choices for firms grouped by ownership control types, profitability and institutional development. Then, logit regression and ordinary least squares regression were applied to examine the determinants of ownership control types in debt maturity structures. Findings: – Compared to privately controlled firms, state-owned enterprises had greater access to long-term debt and used less short-term debt during the sample period. Evidences also indicate that the on-going financial reform has increased the motivation of banks to consider company profitability in their lending decisions. However, state-owned banks still discriminate private firms in allocation of financial resources, particular in less-developed regions. Research limitations/implications: – Due to the research scope and data limitations, the authors cannot take some factors into consideration, such as collateral, guarantee, credit ranking, financing agreement and leasing obligation. Originality/value: – This study extends the existing literature in three ways. First, the authors investigate the bank discrimination problem into the loan term structure. Second, the authors recognise the effect of financial reform on alleviation in bank discrimination problem. Finally, the authors take the consideration of institutional development of firms' location areas in their analyses.